A presença de artistas e ativistas mulheres em jornais impressos paulistanos: um estudo sobre a construção midiática de estereótipos e relações de poder - Cecilio, Laura M (2020)
The main theme of this research is the construction of artists and activists women stereotypes, in reports from the newspapers O Estado de S. Paulo and Folha de S. Paulo, ranging from the Old Republic to the military dictatorship. This dissertation’s hypothesis is that this journalistic media discourse tends to perpetuate power relations that are engendered in relation to the political contexts, happening in a explicitly and tacitly manner, based on discursive practices and the use of images. The theoretical foundation departs from Eric Landowski’s sociosemiotic theory regarding the construction of simulacrum, Judith Butler’s concept of performativity and some topics related to the studies of gender and sexuality in Michel Foucault. The research corpus is composed by reports about Chiquinha Gonzaga (1847 - 1935), Olga Benário Prestes (1908 - 1942), Anita Malfatti (1889 - 1964) and Elis Regina (1945 - 1982). From the analysis, it is concluded that the analyzed media discourses show in their enunciation sets of political-social representations, almost always stereotyped, and that it end up as references of behavior that strengthen valor judgments and reverberate upon the common sense. In this sense, journalism also becomes captured by the power devices that express the same gender problems triggered by them